Ultrafast dynamics of hot carriers in a quasi–two-dimensional electron gas on InSe - Chen, Zhesheng (Proc Natl Acad Sci U S A, 2020)
Two-dimensional electron gases (2DEGs) are at the base of current nanoelectronics because of their exceptional mobilities. Often the accumulation layer forms at polar interfaces with longitudinal optical (LO) modes. In most cases, the many-body screening of the quasi-2DEGs dramatically reduces the Fröhlich scattering strength. Despite the effectiveness of such a process, it has been recurrently proposed that a remote coupling with LO phonons persists even at high carrier concentration. We address this issue by perturbing electrons in an accumulation layer via an ultrafast laser pulse and monitoring their relaxation via time- and momentum-resolved spectroscopy. The cooling rate of excited carriers is monitored at doping level spanning from the semiconducting to the metallic limit. We observe that screening of LO phonons is not as efficient as it would be in a strictly 2D system. The large discrepancy is due to the remote coupling of confined states with the bulk. Our data indicate that the effect of such a remote coupling can be mimicked by a 3D Fröhlich interaction with Thomas–Fermi screening. These conclusions are very general and should apply to field effect transistors (FET) with high- [Formula: see text] dielectric gates, van der Waals heterostructures, and metallic interfaces between insulating oxides.